Republic of Equatorial Guinea : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This Selected Issues paper analyzes macrofinancial linkages in Equatorial Guinea. Insufficient fiscal consolidation in response to falling oil prices and production has translated into arrears accumulation, leading to a sharp deterioration in commercial banks' balance sheets. Although banks' capital and liquidity ratio appear adequate, profitability has been shrinking, owing to weak economic activity and decelerating credit supply. Moreover, recent stress tests reveal a high sensitivity to negative liquidity and asset quality shocks. Financial development remains lackluster, which hurts economic development and effective structural transformation. Finally, strong macrofinancial linkages compounded by regional subsidiary-parent interlinkages call for increased scrutiny.